A two-year examination of the relation between internal and external load and heart rate variability in Australian Rules Football - O`Connor, F. K.; Doering, T. M.; Chapman, N. D.; Ritchie, D. M.; Bartlett, J. D. (Journal of Sports Sciences, 2024)
The relationship between heart rate variability (HRV) and training load in team-sport is unknown. We therefore assessed relations between completed training-load in the previous 1-, 3- and 7-days and waking HRV in professional Australian Rules Football. Linear-mixed models analysed changes in HRV, considering training load from the previous 1-, 3- and 7-days. Total Distance (TD), distance >14.4 km/h (HSR) and >24.9 km/h (Sprint-Distance), duration >85% max heart rate and Rating of Perceived Exertion were included as independent variables. Sub-group analysis of season-phase and years of professional experience was also conducted. Increased three-day Sprint-Distance reduced HRV in the first 8-weeks of pre-season (-13.1 ms, p = 0.03) and across the data collection period (-3.75 ms, p = 0.01). In first-year players, higher previous-day (-63.3 ms, p=0.04) and seven-day TD (-38.2 ms, p = 0.02) reduced HRV, whilst higher seven-day HSR increased HRV (34.5 ms, p = 0.01). In players with five-to-seven years of professional experience, higher three-day (-14.4 ms, p = 0.02) and seven-day TD (-15.7 ms, p = 0.01) reduced HRV, while higher three-day HSR increased HRV (12.5 ms, p = 0.04). In players with greater than eight years of professional experience, higher previous-day Sprint-Distance reduced HRV (-13.1 ms, p < 0.008). Completed training load across the previous 7-days influences HRV, but the relation between variables is complex and influenced by professional experience and season-phase.